Pengertian Tindakan Bullying, Penyebab, Efek, Pencegahan dan Solusi - Chandra Duwita Ela Pradana (Jurnal Syntax Admiration, 2024)
Bullying is an intentional act to hurt another person physically, verbally, or emotionally. Bullying can happen anywhere, including at school, the workplace, and online environments. This research aims to understand bullying, causes of bullying, effects of bullying, and prevention of bullying. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that bullying is caused by several factors including peer environment, family environment and social status. This behavior also has negative effects, including disrupted physical health, mental health problems, and the birth of bullies. Bullying behavior needs to be prevented and solutions formulated, including those that can be implemented wisely by utilizing technological advances, avoiding discriminatory attitudes, instilling affection, socializing through songs, making strict rules about bullying, providing education to perpetrators, providing protection and acting decisively.